The Effect of Country of Origin Image and Corporate Social Responsibility on Customer Loyalty Toward Shiseido Products, with Brand Image as a Mediating Variable in Medan City - Debora Tifani Turnip; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Indonesian Journal Publisher, 2026)
This study aims to analyze the influence of country-of-origin image and corporate social responsibility on consumer loyalty toward Shiseido products in Medan. Additionally, this study examines the role of brand image as a mediating variable in the relationship between country-of-origin image and corporate social responsibility on loyalty. The research sample was selected from Shiseido product users in Medan, resulting in a sample of 140 respondents. The analysis method used in this study is Partial Least Squares-based Structural Equation Modeling (PLS-SEM) using SmartPLS 4 software. The results indicate that country of origin image has a direct, positive, and significant effect on brand image, and corporate social responsibility has a direct, positive, and significant effect on brand image. However, country of origin image has a direct negative but insignificant effect on loyalty, while corporate social responsibility has a positive but insignificant effect on loyalty. Furthermore, brand image has a positive and significant effect on consumer loyalty. Furthermore, the country-of-origin image has a positive and significant indirect effect on loyalty through brand image, and corporate social responsibility has a positive and significant effect on loyalty through brand image. These findings suggest that consumer loyalty toward Shiseido products in Medan can be more effectively built by strengthening the brand image. Therefore, the company needs to strengthen its brand image by highlighting the advantages of its Japanese origin, premium product quality, technological innovation, and a relevant and transparent commitment to corporate social responsibility. An integrated approach between country of origin image, corporate social responsibility, and brand image can help Shiseido increase consumer loyalty and strengthen its competitiveness in the beauty industry.